Two new algal bromophenols from Odonthalia corymbifera. Issue 43 (25th October 2017) - Islam, Md. Reazul; Mikami, Daisuke; Kurihara, Hideyuki
Graphical abstract: Highlights: Two new algal bromophenols consist of brominated hydroxylated benzyl (BHB) units. Odonthalol was a trimer of BHB units connected via ether and methylene bridges. Odonthadione was a hybrid of the BHB unit and a unique cyclopentenedione. Abstract: Two new algal bromophenols, odonthalol and odonthadione, were isolated from the alga Odonthalia corymbifera . Odonthalol was determined as a trimer of brominated hydroxylated benzyl (BHB) units. Three units were connected via ether and methylene bridges. Odonthadione was identified as a hybrid compound of the BHB unit and a unique cyclopentenedione. The cyclopentenedione unit has not been reported from natural origin.